THE DEVELOPMENT OF THE TEMPORAL REFERENCE SYSTEM IN SPANISH: A WALK ON THE VERBAL MORPHOLOGY - Sebastián, Eugenia (Anales de Psicología / Annals of Psychology)
The aim of this study was to assess the development of tense/aspect system in Spanish, within a crosslinguistic project with other four languages. The subjects of the study were 3, 4, 5, and 9 years old children, and a group of adults. Results show that from age 3, Spanish speaking children make use of almost the same verbal forms as 9-year-olds. This is an interesting result because it means that from age 3, children are sensitive to the nature of Spanish grammar, and they include nearly all verbal forms in their discourse. The complexity of the Spanish verbal system does not hinder the child from acquiring aspectual and temporal markers; rather it seems to act as an incentive. Younger children show a clear preference for the use of morphological features to mark notions that older children and adults mark by other non-morphological devices.